how to solve this question
Attachments:
![](https://hi-static.z-dn.net/files/dab/c95aeb8f622fcb1804f8ca6ff724980e.jpg)
Answers
Answered by
1
Heya!!! Mate Your answer will be
![= 2 {x}^{2} + 3x - 90 \\ = 2 {x}^{2} + 12x - 15x - 90 \\ = 2x(x + 6) - 15(x + 6) \\ = (2x - 15)(x + 6) \\ = 2 {x}^{2} + 3x - 90 \\ = 2 {x}^{2} + 12x - 15x - 90 \\ = 2x(x + 6) - 15(x + 6) \\ = (2x - 15)(x + 6) \\](https://tex.z-dn.net/?f=+%3D+2+%7Bx%7D%5E%7B2%7D++%2B+3x+-+90+%5C%5C++%3D+2+%7Bx%7D%5E%7B2%7D++%2B+12x+-+15x+-+90+%5C%5C++%3D+2x%28x+%2B+6%29+-+15%28x++%2B++6%29+%5C%5C++%3D+%282x+-+15%29%28x+%2B+6%29+%5C%5C+)
Hope it helps you mate!!!!!!!!
Hope it helps you mate!!!!!!!!
Similar questions
Computer Science,
8 months ago
Math,
8 months ago
Social Sciences,
1 year ago
Science,
1 year ago
Hindi,
1 year ago
Social Sciences,
1 year ago
Hindi,
1 year ago